1991
DOI: 10.1139/z91-242
|View full text |Cite
|
Sign up to set email alerts
|

Selection of calving sites by Porcupine herd caribou

Abstract: Characteristics of 305 calving sites used by 131 different radio-collared caribou (Rangifer tarandus) cows from the Porcupine herd in northeastern Alaska and the northern Yukon Territory were investigated between 1983 and 1990 to determine the factors influencing calving site selection. Cows selected areas north of the foothills primarily to reduce exposure of calves to predators. Sites dominated by Eriophorum tussocks were selected secondarily for access to newly emerging vegetation. Highest calf mortality oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 4 publications
10
59
1
Order By: Relevance
“…Similar to previous studies (Brown & Theberge, 1985;Gunn & Miller, 1986;Fancy & Whitten, 1991;, the majority of the collared caribou exhib¬ ited some level of site fidelity to calving areas. In some cases the overlap in seasonal ranges during this time period was found to be greater than 30% (Table 5).…”
Section: Discussionsupporting
confidence: 85%
“…Similar to previous studies (Brown & Theberge, 1985;Gunn & Miller, 1986;Fancy & Whitten, 1991;, the majority of the collared caribou exhib¬ ited some level of site fidelity to calving areas. In some cases the overlap in seasonal ranges during this time period was found to be greater than 30% (Table 5).…”
Section: Discussionsupporting
confidence: 85%
“…The 1976 calving area was surveyed in 1986 and no caribou were seen (Gunn & Fournier, 2000a). The possibility that calving shifted northeast of Chantrey Inlet is suggested from observations of calving caribou recorded in 1975, 1985, 1986, 1989and 1991(Gunn & Fournier, 2000a and from seasonal movements of satellite collared cows in 1991-93 (Gunn & Fournier, 2000b). The four satellite-collared cows in 1991-93 showed that caribou wintering south of the Boothia Peninsula toward Baker Lake would calve northeast of Chantrey Inlet (and not Adelaide Peninsula) (Gunn & Fournier, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…We also included those cows with a history of calving on the traditional Beverly calving grounds (south of Garry Lakes) but which had shifted to the Queen Maud Gulf coastal calving ground (Nagy et al, 2011;Gunn et al, 2012). Calving date was based on examination of daily movement rates coupled with spatial movements in GIS, such that calving was determined from a rapid drop in daily movement rate (generally to <2 km/day) and localization, followed by a 5-10 day period of reduced movement (Fancy & Whitten, 1991). The rut and winter distributions were indexed from collar locations on 20 October and 1 February each year, respectively (Gunn et al, 2000).…”
Section: Queen Maud Gulf Calving and Rut Associationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although movement rates have been known to vary among female caribou according to reproductive status (Paré & Huot, 1985;Fancy & Whitten, 1991;Ferguson et al, 1998), high pregnancy rates are pervasive in woodland caribou populations so we assumed by 26 collared female woodland caribou dispersed across three regional populations: the Nottaway, Assinica, and Témiscamie. Primary road networks are also depicted along with the current limit of commercial forestry.…”
Section: Caribou Capture and Gps Telemetrymentioning
confidence: 99%